Wasatiyyah as Translational Practice: Ideology and Gender in Shihab's Qur'anic Translation - Dede Rodin; Saiful Amar; M. Fachrur Rozy (QiST: Journal of Quran and Tafseer Studies, 2026)
Purpose - Despite extensive scholarship on Quraish Shihab's gender hermeneutics in Tafsīr Al-Mishbāh, little attention has been given to his 2013 standalone translation Al-Qur'an dan Maknanya (QM) as an independent ideological text. This study investigates whether and how Shihab's declared principle of wasaṭiyyah (Islamic moderation) is consistently manifested in his translation of gender-related Qur'anic verses. Design/methodology/approach - The study employs a qualitative textual analysis combining Lefevere's rewriting theory, Baker's narrative theory, and Von Flotow's feminist translation strategies. Using close reading, paratextual analysis, and cross-translation comparison, ten verses representing five contested gender clusters—creation ontology, male authority, violence against women, polygamy, and women's testimony—are examined. Findings - The analysis demonstrates that wasaṭiyyah is operationalised through three interrelated translational mechanisms: hermeneutically open lexical choices, ideologically calibrated parenthetical additions, and contextual footnotes. These mechanisms appear consistently across all five verse clusters, albeit with varying intensity. Their most explicit manifestation occurs in the polygamy verses, where a footnote characterises polygamy as a "narrow door accessible only to those in extreme need." Their most subtle application appears in creation ontology, where the translation of nafs wāḥidah preserves interpretive openness and avoids both patriarchal and liberal-feminist extremes. Research implications/limitations - The study focuses exclusively on selected gender-related verses in QM and does not examine the translation's broader theological or socio-political dimensions. Future research may extend the framework to other thematic domains and Qur'anic translations. Originality/value - The study establishes wasaṭiyyah as a verifiable translational practice rather than a mere discursive claim, bridging ideology-based Qur'anic translation studies and Islamic gender hermeneutics while offering a methodological model for evaluating moderation ideologies in Islamic textual production.